MODIFIKASI METODA AASHTO'93 DALAM DISAIN TEBAL LAPISAN TAMBAHAN UNTUK MODEL STRUKTUR SISTEM 3-LAPISAN - Djunaedi Kosasih (Direktorat Bina Teknik Jalan dan Jembatan, 2007)
One of the analytical overlay thickness design methods for flexible pavement structures is the AASHTO'93 standard by employing pavement modult obtained from back calculation process in deflection bowl data. Yet the 2-layered system structure model used in general may result in a theoretical deflection bowl that does not closely match the target deflection bowl data. Croney (1977) suggested to model pavement structure at least as a 3-layered system structure for effective application of analytical design methods. This paper outhnes a modified AASHTO'93 method for analyzing pavement modult of 3-layered system structures resulting from program BackCalc in an overlay design process and specifcally investigates the effects of daily variation in pavement temperature and variation in FWD deflection survey load on pavement modult and on overlay thickness design. Keywords : Overlay Thickness Design, Analytical Method, Pavement Modulus, Back Calculation Process.